Analysis of Online Car Service from User Aspect Using Importance Performance Analysis (IPA) Method - Mochammad Faisol; Sri Wiwoho Mudjanarko (Journal of World Conference (JWC), 2020)
Several factors are considered by consumers in the selection of online transportation such as ease of ordering, appropriate prices and several other factors. The purpose of this study is to determine the effect of services provided online car services to users and determine the factors that need to be improved. This study used a sample of 96 respondents with data analysis using the Importance Performance Analysis method. The results showed that the Online Car (Grab Car) service affected User Satisfaction and the factors that needed to be improved consisted of Timeliness, Attention to, Safety and Environmental Pollution.